Ethnobotany of Tl’azt’en Nation: Plant Use and Gathering Site Characteristics - Shaw, Leona R.; Young, Jane P. (Ethnobiology Letters, 2012)
Aboriginal people have intimate and venerable relationships with the environment, and plants were and still are important for food, medicine, and cultural purposes. The present research is a collaborative project between Tl’azt’en Nation (located in northcentral British Columbia, just north of Fort St. James) and the University of Northern British Columbia (UNBC). The objectives of the study were to collect Traditional Ecological Knowledge (TEK) to gain an understanding of the criteria for gathering individual plants for food or medicine use, and to understand why traditional plant gathering sites may fall out of use. Multiple methods were used to gather information from knowledgeable Tl’azt’enne community members including focus groups, interviews, and field trips. Community members possess deep understandings of plants and their gathering sites. People’s concerns include the loss of TEK and changing landscapes due to the effects of disturbances on their lands. The knowledge gathered and documented throughout the study can be used to promote the preservation of the culture and language of Tl’azt’en Nation